2011
DOI: 10.1007/s11099-011-0043-x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of pepper to waterlogging stress

Abstract: One of the effective ways to address the effects of abnormal climate change on plant is to find germplasms that have better resistance to adverse environments. In this paper, we studied the responses of 5 pepper species Capsicum annuum L. (CA), C. baccatum L. (CB), C. chinense Jacquin. (CC), C. frutescens L. (CF) and C. pubescens Ruiz & Pavon (CP) as well as a wild pepper C. baccatum var. baccatum (CBY) to waterlogging stress. The results showed that warterlogging treatment greatly decreases photosynthetic pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 14 publications
3
33
0
1
Order By: Relevance
“…Resistance to different stress situations have been comparatively studied for the 5 domesticated chili pepper species by Ou et al [20,21]. They found that the investigated Guatemalan C. pubescens pepper had the strongest resistance to low temperatures and was more resistant against drought stress and water logging.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to different stress situations have been comparatively studied for the 5 domesticated chili pepper species by Ou et al [20,21]. They found that the investigated Guatemalan C. pubescens pepper had the strongest resistance to low temperatures and was more resistant against drought stress and water logging.…”
Section: Introductionmentioning
confidence: 99%
“…In order to absorb CO 2 , plants must lose a certain amount of water by transpiration, but this portion did not affect photosynthetic production. This may provide a theoretical basis and practical guidance for reducing transpiration to increase plant WUE without reducing photosynthetic production (Jiang 2004;Ou et al 2011). In practical applications, certain artificial control measures, such as water supply and water conservation, shading at different plant growth stages, and using anti-transpirant materials may reduce plant luxury transpiration and achieve effects of water conservation and increase WUE (Guo et al 2010;Cernusaka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Increased level of proline under waterlogged condition, as compared to normal plants, in genotype CML-204 might be associated with its waterlogging resistant characteristics. The adaptation process of crops to adverse environmental stresses is often accompanied by changes of some compatible osmolytes (Ou et al, 2011). It is well known that abiotic stresses result in increased proline contents in plants (Srivastava et al, 2007).…”
Section: Proline Contentmentioning
confidence: 99%